New species and records of ptyctimous mites (Acari, Oribatida) from Cuba - Niedbała, Wojciech; Ermilov, Sergey G. (Zootaxa, 2015)
An annotated checklist of identified oribatid mites from Cuba, including 16 species, 9 genera and 4 families, is provided. Three new species, Prototritia triangularibus Niedbała sp. nov. (Protoplophoridae), Hoplophthiracarus vinalesensis Niedbała sp. nov. and Protophthiracarus paratripartitus Niedbała sp. nov. (both Steganacaridae), are described from leaf litter. Three species of the subgenus Atropacarus (Hoplophorella)—A. (H.) andrei (Balogh, 1958), A. (H.) brachys Niedbała, 2004 and A. (H.) stilifer (Hammer, 1961)—are recorded in the Cuban mite fauna for the first time.